2007
DOI: 10.1007/s10709-007-9188-8
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of two cytotypes in Bryconamericus aff. iheringii (Characidae): karyotype analysis by C- and G-banding and replication bands

Abstract: Cytogenetic analyses of Bryconamericus aff. iheringii specimens from the upper Paraná River basin (State of Paraná, Brazil) are provided. They had 2n = 52 chromosomes and two cytotypes with variations in their karyotypic formulae: cytotype I with 12 metacentric, 18 submetacentric, 8 subtelocentric and 14 acrocentric chromosomes with a fundamental number (FN) of 90; cytotype II with 8 metacentric, 28 submetacentric, 6 subtelocentric and 10 acrocentric chromosomes with a fundamental number (FN) of 94. Difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…However, a wide variability in karyotypic macrostructure has been a characteristic of this genus ( Table 2). The occurrence of cytotypes in this species has already been documented by de Brito Portela-Castro et al (2008), who observed two cytotypes in the population of Keller River: I -12m+18sm+8st+14a (FN = 90) and II -8m+28sm+6st+10a (FN = 94). Distinct karyotypic formulae have also been documented for Bryconamericus sp B of Piracicaba River (Wasko et al, 1996;Wasko and Galetti Jr., 1998;1999) (FN = 92); and cytotype IV, with 10m+14sm+8st+20a (FN = 84).…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…However, a wide variability in karyotypic macrostructure has been a characteristic of this genus ( Table 2). The occurrence of cytotypes in this species has already been documented by de Brito Portela-Castro et al (2008), who observed two cytotypes in the population of Keller River: I -12m+18sm+8st+14a (FN = 90) and II -8m+28sm+6st+10a (FN = 94). Distinct karyotypic formulae have also been documented for Bryconamericus sp B of Piracicaba River (Wasko et al, 1996;Wasko and Galetti Jr., 1998;1999) (FN = 92); and cytotype IV, with 10m+14sm+8st+20a (FN = 84).…”
Section: Discussionsupporting
confidence: 57%
“…iheringii of Três Bocas Stream and in other species and populations (Capistano et al, 2008;de Brito Portela-Castro et al, 2008;dos Santos et al, 2012), except for Bryconamericus sp E of the Avoadeira Stream, MT, which exhibits 54 chromosomes (Wasko and Galetti Jr., 1998). However, a wide variability in karyotypic macrostructure has been a characteristic of this genus ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are only few surveys on fish fauna in the Ivaí River basin, especially for the tributaries, Barra Bonita River (Maier et al 2008), Bonito River (Viana et al 2013), some streams located in the Perobas Biological Reserve (Delariva & Silva 2013) and a first-order stream in the municipality of Marialva (Araújo et al 2011); and there are few genetic studies with some species of Loricariidae (Zawadzki et al 2004, Portela-Castro et al 2007, Paiva et al 2013 or ecological studies (Luiz et al 2003, Luiz et al 2005) and description of new species (Graça & Pavanelli 2008, Roxo et al 2014, Tencatt et al 2014, Zawadzki et al 2016) with fish of this basin.…”
Section: Introductionmentioning
confidence: 99%